Incidence and nature of farm-related injuries among children aged 6-15 during a 10-year period in one region Poland - Sosnowska, Stefania; Kostka, Tomasz (Central European Journal of Public Health, 2007)
The health risks among children in “new” and “old” members of the European Union seem to be different. Farms are the most frequent place of injuries among children living in rural areas in Poland. Our aim is to present data on the farm-related injuries conditions among children aged 6–15 in one large region in Poland. The analysis has been made on the basis of information collected from the Farmers’ Insurance Fund in Włocławek, which registers all farm-related injuries reported within the Włocławek Province. Over the 10-year study period 449 injuries were recorded (1.29 injuries per 1000 person-years). Among all victims there were 132 girls (29.4% of the total) and 317 boys. 14-year-old children fell victims of injuries most frequently (20.0% of all injuries). The highest number of injuries was recorded during the summer season. The injuries resulted mainly from falls or slips (47.2%) and falling from high altitudes (22.9% of all injuries). Individual and unattended works accounted for 37.5% of cases while 30.4% of all injuries happened while children were assisting in the work performed by adults. The sites were farm facilities (29.0%), farmyard (23.8%), around farm facilities (13.1%), pastures and meadows (11.1%), fi elds (9.1%), roads leading to houses or farm facilities (7.6%) and home (6.2%). We conclude that 13–15-year-old boys falling during an individual unattended work or while assisting in the work performed by adults, inside and around farm facilities, and during summer months, were the most frequent victims of injuries on farms. Information obtained in this study may be helpful in developing and implementing injury prevention strategies tailored to the Central-Eastern European agricultural realities.
Keywords: Data Interpretation, Statistical; Polsko; zemědělství; Safety; Poland; Agriculture; Humans; Accidents; úrazy a nehody; bezpečnost; interpretace statistických dat; úrazy pádem; Accidental Falls; dítě; lidé; Child